Large Device-Related Thrombus Detected following Symptoms of Transient Ischemic Attack - Osayi Lawani; Edward Baptista (Case Reports in Cardiology)
As an independent risk factor for stroke, atrial fibrillation has been shown to be associated with a fivefold increase in the cause of embolic stroke in comparison to healthy individuals without atrial fibrillation. This risk may be compounded by other factors; however, the main probable cause of stroke leading from atrial fibrillation is thrombus formation in the left atrial appendage. In patients for whom anticoagulation is contraindicated, left atrial appendage occlusion has become a leading alternative option for therapeutic prevention of thromboembolism and stroke in patients with this condition. Unfortunately, these devices (particularly the WATCHMAN) have been associated with a 3-6% incidence of intracardiac thrombus development postimplantation. Some risk factors for the development of device-related thrombus are high platelet count, permanent atrial fibrillation, resistance to clopidogrel, and prior transient ischemic attack or stroke. Despite following an anticoagulant regimen, thrombus formation was reported in 5.6% of participants of a randomized clinical trial, and further analysis showed that some of these patients continued to develop either ischemic stroke or thromboembolism five years later as compared to patients without initial thrombus development. We present a case of an elderly male with prior history of stroke and transient ischemic attack who developed a large device-related thrombus five months following WATCHMAN FLX™ implantation. Currently, there are no specific recommendations on the management of this rare complication; however, we discuss possible consideration of initially prolonging anticoagulation therapy following implantation for high-risk individuals, as there is an increased possibility for thrombus formation in this population. Management options should continue to be studied for therapeutic benefit in streamlining postprocedural therapy and improve future outcomes in the use of left atrial appendage occlusion devices, as well as continual thrombus prevention.